Analysis Dumbbell Wrist Exercise Against Backhand Overhead Lob Badminton Players - Yogaswara, Andre; Pratama, Muchammad Sendyyudha (Quality in Sport, 2022)
To ascertain the impact of 0.5 kg and 1 kg dumbbell wrist exercises on beginning badminton players' backhand overhead lobs. (2) contrasting the efficiency of 0.5 kg and 1 kg dumbbell wrist exercises with a novice badminton player's backhand overhead lob? The research method employed is an experimental approach, and the treatment consists of 0.5 kg and 1 kg dumbbell wrist exercises, performed three times per week for a period of six weeks. A sample of 12 players from PB Sehat Semarang was split into two groups of six each, representing the population. Backhand overhead lob test: a tool for gathering data. The outcomes of the hypothesis analysis were t-count group A 4.029 and group B t-count 5.838 while the t-table from degrees of freedom n-1 + n2 - 2 is 6 + 6 - 2 = 10 and the level of confidence = 5% is 2.28. The study's main finding is that (1) beginners' backhand overhead lobs are affected by wrist exercises using 0.5kg and 1kg dumbbells. (2) The 0.5 kg dumbbell wrist exercise method and the 1 kg dumbbell wrist exercise differ in how well they increase the ability of the backhand overhead lob, but the 0.5 kg dumbbell wrist exercise has a more noticeable impact than the 1 kg dumbbell wrist exercise.